Emergency Management in Eating Disorders - Needham, Heather; Ferguson, Elizabeth; Takemoto, Darcie; Idicula, Sindhu (Adolescent Psychiatry, 2019)
Aims and Scope: Eating disorders commonly present during the adolescent and young adult years, and are complex in that they are a group of psychiatric diagnoses with medical complications. Methods: The diagnosis of an eating disorder can often go undetected while a patient is being evaluated for organic causes of weight loss. Anorexia nervosa, in particular, has the highest mortality rate of any psychiatric diagnosis. In the Diagnostic and Statistical Manual of Mental Disorders 5th Edition (DSM-5), there are several diagnoses that are classified as eating or feeding disorders. Conclusion: This article will discuss anorexia nervosa and bulimia nervosa, with a focus on medical and psychiatric emergencies that are important for primary care providers to keep in mind when caring for adolescents and young adults.
Keywords: young adult